Development of enterprise motivation policy (Economics and region, 2025)
The article presents a comprehensive study of the theoretical and methodological foundations for the formation of an enterprise’s motivation policy in the conditions of dynamic changes in the socio-economic environment. Motivation policy is considered not only as a system of incentive tools but as a strategically oriented and adaptive management mechanism that ensures sustainable productivity and long-term competitiveness of the enterprise. The authors emphasize that modern motivation must integrate both tangible and intangible components, including flexible working conditions, opportunities for professional development, recognition, participation in decision-making, and alignment with organizational values. The study provides a critical analysis of recent scientific publications by Ukrainian and foreign scholars and systematizes the evolution of motivation concepts — from classical administrative theories to contemporary human-centric and hybrid models. Particular attention is given to the specifics of motivating employees under conditions of uncertainty, war, and post-crisis recovery, which require the rethinking of traditional incentive schemes and the development of personalized approaches based on generational differences and value shifts. The relevance of forming a motivation policy that balances economic interests with the social and psychological needs of employees is substantiated. The paper outlines key components of a motivation policy: material and non-material incentives, organizational support, transparent evaluation mechanisms, corporate culture, and strategic communication. The importance of ESG principles and social responsibility as new motivators is also discussed. Based on the conducted analysis, practical recommendations are proposed for the development of effective motivational systems focused on innovation, inclusivity, and value-driven leadership. The scientific novelty of the article lies in the comprehensive typology of modern motivation approaches and the proposed model of building an adaptive and human-oriented motivation policy in enterprises of various sectors.
Keywords: motivation; motivation policy; strategic human resource management; adaptability; employee needs; incentives; organizational values; employee engagement; leadership; ESG